BASF to build new plastic additives plant in Shanghai to harness Chinese growth opportunities. Issue 5 (May 2017) - Unknown
Abstract : German chemicals giant BASF plans to build a new plastic additives plant at its Caojing site in Shanghai, China, as part of the previously announced €200 million global investment in its plastic additives production network [ ADPO, January 2017]. This world-scale plant, with an annual capacity of 42 000 tonnes, will produce antioxidants and associated forms and blends. Construction is expected to be completed in 2019, with commercial operation to start by early 2020.